Chapter 4 Developing the meta-inference in mixed methods research through successive integration of claims - Schoonenboom, Judith (Taylor & Francis, 2022)
This handbook reviews different mixed methods and integration ideas with contributions from scholars across the globe, accelerating discussion of mixed and integrated methods across a broad range of disciplines, including education, arts-based analyses, health research, and work in developing nations, as well as via special topics such as psychometrics and media research. The authors encourage and guide integration by updated design thinking, and presentation of analytic models and software.